Correlation between browning index and browning parameters during the senesence of longan peel - Sarana Sommano (2018)
The correlations of browning index of longan peel with different browning parameters were studied. The index was determined by rating the visible browning appearance of longan peels stored for eight days at 25°C by eight individuals. The result was then tested for correlation with CIE color parameters (L, a, and b), hue angle (h°), polyphenoloxidase activity, and percentage of ion leakage of the peels. The correlation was also confirmed using oxalic acid solution as an effective anti-browning agent. The results suggested that with or without the organic acid treatment, good correlations were observed only with a value and hue angle (h°), indicating alteration of the darkness. Polyphenoloxidase activity as well as the leakage, however, did not correlate with browning index. © Taylor & Francis Group, LLC.